Experimental Venous Thrombosis in Rats - Nordöy, Arne (Thrombosis and Haemostasis, 1963)
1. Thrombosis in rats were produced by Blake et al.’s technique of application of formalin solution to the jugular vein. The incidence of thrombosis produced by a 10% (v/v) formalin in 65% methanol solution and observed after 24 hours was 30% ± 4.6 S. D.2. The administration of 100 mg EACA 1,000 g body weight orally every fourth hour for 24 hours increased the incidence of thrombosis about twice (to about 65%).A single dose of 400 mg EACA 1,000 g body weight had a slight effect only.3. EACA increased markedly the antifibrinolytic activity in plasma with a maximum after 3—5 hours oral administration. A moderate increase in the fibrinogen concentration was observed in all groups.4. Global tests for plasma coagulation, the platelet count and the number of adhesive platelets were not significantly influenced by the administration of EACA.